Synthesis and structural analysis of the anilides of glucuronic acid and orientation of the groups on the carbohydrate scaffolding - Tosin, M; O'Brien, C; Fitzpatrick, GM; Muller-Bunz, H; Glass, WK; Murphy, PV (Journal of organic chemistry, 2005)
The synthesis of anilides derived from glucuronic acid is described. Secondary anilides had a Z configuration in the solid state and showed intramolecular and intermolecular hydrogen bonding. However, on the basis of NMR and IR studies, there was generally no evidence for the same hydrogen bonding in solution. Tertiary anilides showed a strong preference for the E configuration on the basis of NOE studies and molecular mechanics calculations. The alkylation of the secondary anilides induces a configurational switch that alters the orientation of the aromatic group with respect to the pyranose, which has relevance for presentation or orientation of pharmacophoric groups on carbohydrate scaffolds.